The efficacy and acceptability of the Triple P: Positive Parenting Program with Turkish parents. Issue 3 (23rd June 2020) - Arkan, Burcu; Güvenir, Taner; Ralph, Alan; Day, Jamin
Abstract: Aim: To evaluate the effectiveness of Group Teen Triple P with parents who have behaviorally disturbed adolescents. Methods: The research was conducted in an experimental manner. The sample was 76 parents who were grouped as 38 cases and 38 controls with a block randomization method. Data were collected using the Family Background Questionnaire, General Health Questionnaire (GHQ‐12), Strengths and Difficulties Questionnaire (SDQ), Conflict Behavior Questionnaire (CBQ), and Parent Satisfaction Questionnaire. Group Teen Triple P Program was implemented with the case group for 8 weeks. Data were collected immediately after the program and again after 3 months. Data were evaluated using variance analysis, t  test, χ 2 test, multivariate analysis of covariance, and analysis of covariance test. Results: It was found that participation in Group Teen Triple P resulted in the improvement of parental mental health, decreased problematic behavior of the adolescents, and fewer problems between adolescents and their parents. Conclusion: Group Teen Triple P should be made available to more parents of adolescents in Turkey.